Mental healthcare staff well‐being and burnout: A narrative review of trends, causes, implications, and recommendations for future interventions - Johnson, Judith; Hall, Louise H.; Berzins, Kathryn; Baker, John; Melling, Kathryn; Thompson, Carl (International journal of mental health nursing, 2018)
Rising levels of burnout and poor well‐being in healthcare staff are an international concern for health systems. The need to improve well‐being and reduce burnout has long been acknowledged, but few interventions target mental healthcare staff, and minimal improvements have been seen in services. This review aimed to examine the problem of burnout and well‐being in mental healthcare staff and to present recommendations for future research and interventions. A discursive review was undertaken examining trends, causes, implications, and interventions in burnout and well‐being in healthcare staff working in mental health services. Data were drawn from national surveys, reports, and peer‐reviewed journal articles. These show that staff in mental healthcare report poorer well‐being than staff in other healthcare sectors. Poorer well‐being and higher burnout are associated with poorer quality and safety of patient care, higher absenteeism, and higher turnover rates. Interventions are effective, but effect sizes are small. The review concludes that grounding interventions in the research literature, emphasizing the positive aspects of interventions to staff, building stronger links between healthcare organizations and universities, and designing interventions targeting burnout and improved patient care together may improve the effectiveness and uptake of interventions by staff.